VINER FINTECH (VIDEO EXPLAINER FINTECH) SEBAGAI UPAYA PENINGKATAN PENGETAHUAN MAHASISWA MENGENAI PINJAMAN ONLINE DALAM PANDANGAN ISLAM - Dikara Nur Izabah; Dilla Meliani; Elza Lystia Oktaviani; Rita Nurjanah; Ani Nur Aeni (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2022)
There have currently emerged online loans that provide ease for people to gain credit access. This online loan on the one hand provides convenience to the community but on the other hand it can be detrimental to the community, such as the amount of bills that do not match the money borrowed, debt collection is done by terrorizing and embarrassing customers, interest continues to increase where it includes usury and in the view of Islamic illegitimatehis. Related to that, then it is important to examine how people know about online loans and how Islam views the phenomenon. The purpose of this writing is to find out how the knowledge of the public in particular college students is related to how the online lending law is in the Islamic perspective, through the appearance of animated videos in the form of video explorer. The research method used in this study is Design and Development (D&D). The research results show the recapitulation of college students' knowledge of the online lending phenomenon is in the good category, accounting for 69.12%. Of the 38 respondents who were able to answer correctly, problem number 1-5 was 56.32% with sufficient understanding according to criteria, problem number 6-10 was 72.1% with good understanding according to criteria, problem number 11-15 was 78.94% with good understanding according to criteria. Then it is possible to infer the understanding of the student to the online loan phenomenon based on the test conducted after watching the video explorer is good with an average score of 69.12%.